COMPREHENSIVE REVIEW OF POST-COVID-19 INFECTIONS: A MULTIFACETED ANALYSIS - SHENDE, VIJAYALAXMI A. (International Journal of Current Pharmaceutical Research, 2023)
This comprehensive review offers a multifaceted analysis of post-COVID-19 infections, encompassing diverse aspects of this evolving health concern. In the realm of symptomatology, we explore both common and rare symptoms observed in individuals recovering from COVID-19, shedding light on the intricacies of post-acute sequelae. Moving forward, we delve into the association between COVID-19 and diabetes along with glucose intolerance, analyzing the incidence of these metabolic conditions in the post-COVID era. Another critical dimension of our analysis is the examination of the potential direct association between COVID-19 and obesity, considering the implications of this relationship on public health. Furthermore, we trace the evolution of treatment strategies across the pandemic's waves, providing a comprehensive review of approaches taken during the 1st, 2nd, and 3rd waves, along with discussions on current government-recommended treatment and management protocols. As we navigate the ongoing challenges presented by post-COVID-19 conditions, this article aims to serve as a valuable resource for healthcare professionals, researchers, and individuals seeking a deeper understanding of the multifaceted nature of these infections and their implications for healthcare and public health strategies. Concluding remarks, this comprehensive review underscores the complex landscape of post-COVID-19 infections, ranging from symptomatology to metabolic associations and treatment strategies. It serves as a vital resource for understanding the multifaceted implications of these conditions on healthcare and public health efforts.